1983
DOI: 10.1200/jco.1983.1.8.496
|View full text |Cite
|
Sign up to set email alerts
|

Human tumor cell heterogeneity and metastasis.

Abstract: Heterogeneity within malignant neoplasms, although described for many years by pathologists, has only recently been extensively studied in the laboratory. It is now accepted that most tumors are composed of subpopulations of cells that differ in many phenotypic characteristics including the ability to form a metastasis. Cells with the capacity to metastasize are the ones most likely to prove lethal to the patient since clinicians can often control the primary neoplasm with surgery or radiotherapy. In this repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…The metastatic cascade is a complex series of processes including angiogenesis, intravasation of tumor cells, transport by the circulation, adhesive interaction with endothelial cells, extravasation, and colonization of the target organ (38)(39)(40)(41). Only a small subpopulation of cells from heterogeneous primary tumors appears able to form metastatic colonies (42,43). The survival and proliferation of these metastatic cells depend on various biological properties, such as resistance to host defense mechanisms, regulation of adhesion molecules, and enzymes that degrade basement membranes (39,40,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The metastatic cascade is a complex series of processes including angiogenesis, intravasation of tumor cells, transport by the circulation, adhesive interaction with endothelial cells, extravasation, and colonization of the target organ (38)(39)(40)(41). Only a small subpopulation of cells from heterogeneous primary tumors appears able to form metastatic colonies (42,43). The survival and proliferation of these metastatic cells depend on various biological properties, such as resistance to host defense mechanisms, regulation of adhesion molecules, and enzymes that degrade basement membranes (39,40,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be due to the undifferentiated component of the histology. The median number of removed pelvic LNs was 16 (range, [15][16][17][18][19][20][21][22][23][24][25][26][27], the median number of removed para-aortic LNs was 8 (range, 4-30), and the median number of positive paraaortic LNs was 1 (range, 1-4). All patients had FIGO stage IIIC2 disease.…”
Section: Resultsmentioning
confidence: 99%
“…19 Tumor cells first develop the capacity for local tissue invasion and then spread through gaps between endothelial cells into the lymph-vascular space of the stroma, and, once LVSI has occurred, tumor cells have the potential for metastatic spread to other sites. 20 LVSI may lead to tumor emboli invading pelvic and para-aortic LNs. Previous investigators suggested that LVSI and other factors correlated significantly with para-aortic LNM.…”
Section: Discussionmentioning
confidence: 99%
“…In its simplest model, a solid tumor may be viewed as an organ containing multiple cell types that act in concert to promote tumor growth [Spremulli andDexter, 1983, Dexter et al, 1978]. Thus, drugs that target a single type of cell for therapeutic intervention may only provide marginal anti-tumor effect.…”
Section: Introductionmentioning
confidence: 98%